Conflicts occurring due to the application of different legal inheritance systems in Indonesia - Suwarti, Suwarti; Khunmay, Decha; Abannokovya, Stepan (Faculty of Law, University of Muhammadiyah Malang, 2022)
The Republic of Indonesia applies three legal systems on inheritance, namely the Islamic law, the Civil Code, and the Indigenous law. Conflicts occur when families use different legal systems in splitting inheritance. This paper aims to analyze: (1) The considerations of the judge in deciding the right of heirs with different religions to obtain inheritance; (2) Whether or not using wasiat wajibah in distributing inheritance to non-Muslim heirs violates Islamic laws; and (3) The legal efforts which may be taken if heirs who follow a different religion from the decedent do not obtain an inheritance. This is normative prescriptive legal research employing a comparative approach. Primary and secondary data were collected from the literature review. Results showed that the Supreme Court judge decided that a non-Muslim widow has the right to obtain an inheritance from her deceased Muslim husband based on the wasiat wajibah stipulations, considering that the widow had been married to the deceased for 18 years. Referring to wasiat wajibah to give inheritance to non-Muslim heirs does not violate Islamic law, in which the maximum amount is a third of the inheritance. This paper suggests two ways to resolve conflicts on inheritance: (1) Let the inheritance laws be plural. If there are legal conflicts, they can be resolved in court, (2) Unify the laws by creating new inheritance national laws to achieve national unity. This research provides novelty, recalling that there has not been any previous research on the same theme in Ternate City.